Aquaculture Intrusion Detection System based on IoT Mesh network - Ro, Cheulwoo; Kim, Taehee (IJRDO -Journal of Computer Science Engineering, 2016)
Aquaculture industry has been suffering significant losses from intruders and fishing boats. To eradicate such intrusions, we suggest a solution for intrusion detection based on Bluetooth mesh communication. Bluetooth Smart mesh modules incorporated with human motion detect sensors such as PIR on buoys could form an active net for detection of humans and objects. Automatically, Solar power can generate sufficient power for each modules. One mesh module which has 3G communication as a mother module will communicate with monitoring system. This paper illustrates a proposed solution for aquaculture intrusion detection that claims novel efficiency by employing Bluetooth Smart mesh networks and an IoT platform.